‘The Improvement of Educational Standarts of Academicians by Using Various Tools Offered by The Behavioural Change Matrix’ - Iyilikci, Necip Ozgur (European Scientific Journal, ESJ, 2017)
Within the bounds of behavioural economics, this paper offers some commitment tools for academicians by changing their behaviours in some specific issues to explore better way of improving educational quality. Increasing classroom participation, failure to assess students’ exam papers fairly because of the false impression of the first answer, preferring complicated and confusing teahing methods due to reasons originating from heuristic knowledge; and lack of attention and available advisory bodies to students in nonclass time are considered among these. Depending on willingness and awaresness of lecturer, behavioural change matrix offers some commitment tools that can change their behaviours for attaining higher overall academic performance.